1996
DOI: 10.1073/pnas.93.23.12861
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cyclin D1 by simian virus 40 small tumor antigen

Abstract: Cell-cycle progression is mediated by a coordinated interaction between cyclin-dependent kinases and their target proteins including the pRB and E2F͞DP-1 complexes. Immunoneutralization and antisense experiments have established that the abundance of cyclin D1, a regulatory subunit of the cyclin-dependent kinases, may be rate-limiting for G 1 phase progression of the cell cycle. Simian virus 40 (SV40) small tumor (t) antigen is capable of promoting G 1 phase progression and augments substantially the efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
153
2
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(163 citation statements)
references
References 67 publications
7
153
2
1
Order By: Relevance
“…(2) PP2A represses AP-1 activity by dephosphorylation of c-Jun on Ser-63 (Alberts et al, 1993;AlMurrani et al, 1999;Ramirez et al, 2005). (3) c-Jun enhances cell proliferation through induction of cyclin D1 transcription, shown by several reports (Watanabe et al, 1996;Shiozawa et al, 2004;Whang et al, 2005). The possibility that the involvement of c-Jun in the mechanism of LMB-induced reduction of cyclin D1 expression was further supported by our findings: (1) serum-induced cyclin D1 expression is required for AP-1 site in the promoter region of cyclin D1 gene, and the residual promoter activity of AP-1 site-deleted or pointmutated cyclin D1 promoter construct is no longer inhibited by LMB treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) PP2A represses AP-1 activity by dephosphorylation of c-Jun on Ser-63 (Alberts et al, 1993;AlMurrani et al, 1999;Ramirez et al, 2005). (3) c-Jun enhances cell proliferation through induction of cyclin D1 transcription, shown by several reports (Watanabe et al, 1996;Shiozawa et al, 2004;Whang et al, 2005). The possibility that the involvement of c-Jun in the mechanism of LMB-induced reduction of cyclin D1 expression was further supported by our findings: (1) serum-induced cyclin D1 expression is required for AP-1 site in the promoter region of cyclin D1 gene, and the residual promoter activity of AP-1 site-deleted or pointmutated cyclin D1 promoter construct is no longer inhibited by LMB treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The reporter constructs of the human cyclin D1 promoter were a gift from Richard G Pestell (Watanabe et al, 1996;Albanese et al, 1999). A 1745-bp fragment of the human cyclin D1 gene was obtained by polymerase chain reaction (PCR) and cloned into the plasmid pGL3-Basic (Promega, Madison, MA, USA) to generate -1745D1LUC.…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…Accumulation of this complex leads to the activation of the kinases that phosphorylate and inactivate the tumor suppressor retinoblastoma, a necessary step for cell cycle progression through G1-to-S phases (Harbour and Dean, 2000). The expression levels of cyclin D1 have been shown to be rate limiting in cellular proliferation induced by a variety of stimuli (Ohtsubo and Roberts, 1993;Quelle et al, 1993;Albanese et al, 1995;Watanabe et al, 1996), and an increased expression of cyclin D1 has been observed in several tumors (Wang et al, 1994;Arber et al, 1996;Zhang et al, 1997;Albanese et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Known cellular targets for small t are hsc70 (Srinivasan et al, 1997) and protein phosphatase 2A (Pallas et al, 1990;Yang et al, 1991). Other reported functions of small t include transcriptional activation of promoters of AP-1 (Frost et al, 1994) cyclin A (Porras et al, 1999), and cyclin D1 (Watanabe et al, 1996), repression of c-fos promoters (Wang et al, 1994), and down-regulation of the cdk inhibitor p27 KIP1 (Porras et al, 1999).…”
Section: Discussionmentioning
confidence: 99%